Effect of Cytokinins and Carbenicillin on In vitro Axillary-Shoot Growth of Albizia [Albizia falcataria (L.) Fosberg] - Sri Nanan Widiyanto; Mirah Dila Sari; Rina Ratnasih Irwanto (Institut Teknologi Bandung, 2008)
Effect of N6-benzylaminopurine (BA), 6-furfurylaminopurine (kinetin) and carbenicillin on axillary-shoot growth ofalbizia [Albizia falcataria (L.) Fosberg] from cotyledonary node-segments were evaluated in vitro. Shoot inductionmedium was composed of Murashige and Skoog (MS) basal medium with or without the addition of BA or kinetin. Thesensitivity to carbenicillin was tested using shoot induction medium with the addition of carbenicillin at 10-50 mg/L.The results showed that the optimal axillary-shoot growth was observed on medium containing 2.2 Î¼M BA and 2.3 Î¼Mkinetin, which reached the average of 36.0Â±2,2 mm shoot-length and 2.9Â±1,1 nodes/shoot in four weeks. The addition ofcarbenicillin inhibited the axillary-shoot growth, shown by 6.1-11.5 mm of shoot length of and 1.0-11.1 of nodes/shoot.A total of 60 shoots were elongated and rooted in in vitro condition on MS medium without growth regulator. Allplantlets were successfully transferred to a soil-sand medium (1:1) and grew well in the green-house.